Investigating the feasibility of using asphalt pavements as a source of heating - Dehdezi, Pejman Keikhaei; Dawson, Andrew R.; Hall, Matthew R.; Casey, Sean; Miao, Fei (2012)
This paper evaluates the feasibility of using asphalt pavements as solar energy collectors with copper pipes embedded below the surfaces. Quartzite was investigated as a replacement for limestone aggregate in asphalt for thermal enhancement. Samples of both asphalt types were tested for indirect stiffness modulus, indirect fatigue, permanent deformation and thermal conductivity. The pipe networks system was also tested. The results indicate that limestone has a better performance in load bearing capacity except fatigue life but the thermal conductivity of the quartzite mixture is higher. With a greater thermal conductivity in the upper layer, the thermal efficiency of the network can be significantly improved.